Innovation integration of Islamic values in learning environmental themes in biology education - H. Husamah; Hadi Suwono; Hadi Nur; Agus Dharmawan (University of Muhammadiyah Malang, 2022)
This article aims to analyze the innovation of integrating the values ​​of Islamic Values in learning environmental themes in the Biology Education Study Program at Muhammadiyah Higher Education. It is library research with qualitative data based on the secondary data. The source triangulation technique was employed to check the data validity. The obtained data were analyzed using descriptive qualitative analysis using VOSviewer software, which are described through the results of behaviour and sentences observed by the researcher. Content analysis was employed as the analysis technique. the results showe 17 formulations of the importance and urgency of Islamic Values and 12 formulations of Islamic Values ​​and their integration in learning environmental themes. This means that Islamic Values need to be integrated into learning environmental themes in the Biology Education Study Program at Muhammadiyah Higher Education along with the learning model. Among the model that can be used is integrative STAD type Cooperative Learning and Project-Based Learning